A Truncated Multi-Thiol Aptamer-Based SARS-CoV-2 Electrochemical Biosensor: Towards Variant-Specific Point-of-Care Detection with Optimized Fabrication - Sergio Roberto Molina Ramirez; Nafiseh Samiseresht; Mateo Alejandro Martínez-Roque; Ferdinando Catania; Kevin Graef; Martin Rabe; Andreas Offenhäusser; Dirk Mayer; Gabriela Figueroa-Miranda (Biosensors)
With the goal of fast and accurate diagnosis of infectious diseases, this study presents a novel electrochemical biosensor that employs a refined aptamer (C9t) for the detection of spike (S) protein SARS-CoV-2 variants in a flexible multielectrode aptasensor array with PoC capabilities. Two aptamer modifications were employed: removing the primer binding sites and including two dithiol phosphoramidite anchor molecules. Thus, reducing fabrication time from 24 to 3 h and increasing the stability and sparseness for multi-thiol aptasensors compared to a standard aptasensor using single thiols, without a reduction in aptamer density. The biosensor fabrication, optimization, and detection were verified in detail by electrochemistry, QCM-D, SPR, and XPS. The analyte–receptor binding was further confirmed spectroscopically at the level of individual molecules by AFM-IR. The aptasensor possesses a low limit of detection (8.0 fg/mL), the highest sensitivity reported for S protein (209.5 signal per concentration decade), and a wide dynamic detection range (8.0 fg/mL–38 ng/mL) in nasopharyngeal samples, covering the clinically relevant range. Furthermore, the C9t aptasensor showed high selectivity for SARS-CoV-2 S proteins over biomarkers for MERS-CoV, RSV, and Influenza. Even more, it showed a three times higher sensitivity for the Omicron in comparison to the Wuhan strain (wild type), alpha, and beta variants of the SARS-CoV-2 virus. Those results demonstrate the creation of an affordable and variant-selective refined C9t aptasensor that outperformed current rapid diagnosis tests.